(untitled) (CIPEEX, 2025)
Rural credit bonds are financial instruments used in agribusiness to circulate wealth, their main and most important function is to facilitate the financing of Brazilian agricultural activity. Decree-Law No. 167/67 in its article 42, § 2°, regulates the purchase and sale of agricultural goods in installments through the NPR (Rural Promissory Note). The credit title offers legal security for both the issuer and the creditor. This work addresses aspects of the application of the rural credit title-promissory note to boost Brazilian agribusiness. The objective is to discuss the Brazilian doctrinal understanding in relation to the rural credit title, in particular, the promissory note and its relevance for the national economy. The methodology applied is qualitative, given that this is a specific and qualified study of the importance of using the promissory note in rural areas for financing agricultural production. Doctrines and lectures on the topic were used. As a result and conclusion, in short, rural promissory notes represent great value in the Brazilian economic system, given the simplicity of the title and the legal security it offers, being essential for the expansion of agribusiness.